(untitled) (Perner’s Contacts, 2019)
The paper deals with the constructional design of kinematic arrangement of mechanism with rotating cylinders and its use especially in piston combustion engines (spark-ignition engine and diesel engine), which may be two or four-stroke engines. The entire mechanism will be designed with the aim to completely eliminate the side (normal) force acting on the piston by ensuring a zero angle of connecting rod swing β at each mechanism position. This will be ensured by connecting rod’s kinematics – it should only be moved in the cylinder axis.